Chronic insomnia disorder as risk factor for stroke: a systematic review - Luiz Augusto Soares Silva; Mateus Molin do Amaral; Vanise Grassi; André Luiz Rodrigues Palmeira (Arquivos de Neuro-Psiquiatria)
Background Stroke is one of the main causes of mortality worldwide. Nonetheless, there are still risk factors that have not been fully elucidated, such as chronic insomnia disorder. Objective To evaluate the association between chronic insomnia disorder and the risk of stroke in adults, through a systematic review. Methods Multiple studies available in the Embase, Lilacs, and Medline platforms were evaluated in English, Spanish, French, and Portuguese. The selection of papers was restricted to those that had investigated the association between chronic insomnia disorder and stroke in adults, regardless of gender or nationality, without a previous history of stroke. The data was extracted with the Cochrane Effective Practice and Organization of Care (EPOC) form. The risk of bias was evaluated by the EPOC Risk of bias tool. Results A total of 138 articles were identified. After a detailed evaluation with the eligibility criteria, four articles were included in the present systematic review. Three of them recognized the association between chronic insomnia disorder and stroke. The comparative analysis was limited, since the studies used distinct insomnia classifications. Regarding the risk of bias, the analysis displayed an important risk in the selection and allocation of participants, besides the use of own insomnia diagnosis criteria, disrespecting chronology and factors indicated by already established classifications. Conclusions There is not enough data to determine that chronic insomnia disorder is a risk factor for stroke. The present study points out the existence of a possible relationship between insomnia disorder and stroke, suggesting that further studies adopt standardized criteria and instruments.